1972
DOI: 10.1139/v72-485
|View full text |Cite
|
Sign up to set email alerts
|

Metals Intercalated in Graphite. I. Reduction and Oxidation

Abstract: Potassium in graphite shows distinctive reducing properties towards carbonyls. The reaction products can be related to a mechanism similar to electrochemical reduction. The steric orientation of the reduction can be explained by the particular structure of potassium-graphite.Chromic anhydride in graphite offers a new selective method of preparation of aldehydes from the corresponding primary alcohol. This method is characterized by its specificity, high yields and a simple experimental procedure.Le potassium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(32 citation statements)
references
References 1 publication
0
32
0
Order By: Relevance
“…18-crown-6 (18-C-6) and [2.2.2]cryptand (crypt-222) were purchased from Sigma-Aldrich and dried by dissolving in diethyl ether and storing over sieves for several days, followed by removal of the sieves and solvent. tbs LH6, 1 ( tbs L)Fe 3 (thf) (see Supporting Information), and potassium graphite (KC 8 ) 17 were prepared according to literature procedures. All other reagents were purchased from commercial vendors and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…18-crown-6 (18-C-6) and [2.2.2]cryptand (crypt-222) were purchased from Sigma-Aldrich and dried by dissolving in diethyl ether and storing over sieves for several days, followed by removal of the sieves and solvent. tbs LH6, 1 ( tbs L)Fe 3 (thf) (see Supporting Information), and potassium graphite (KC 8 ) 17 were prepared according to literature procedures. All other reagents were purchased from commercial vendors and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Complex 2, Na/Hg and KC 8 were prepared according to published procedures. 14,41,42 Elemental analyses were obtained from the Analytical Laboratories at Friedrich-Alexander-University and Georg-August-University, respectively. IR spectra were recorded as nujol mulls between KBr disks using a JASCO FT/ IR 4100 Spectrometer.…”
Section: General Considerationsmentioning
confidence: 99%
“…It has been found that a chromic acid on graphite -supposedly an intercalated compound -prepared by heating a mixture of chromic anhydride with graphite under reduced pressure, may act as a specific oxidant for primary alcohols [215]. Table 48 summarizes a choice of feasible reactions [215]. Yields are generally good, even with sensitive structures such as terpenes or allylic systems.…”
Section: D) Chromic Acid On Graphitementioning
confidence: 99%